2022
DOI: 10.1177/10690727221099867
|View full text |Cite
|
Sign up to set email alerts
|

How Dispositional Gratitude Shapes Employee Well-being and Organizational Commitment: The Mediating Roles of Leader-Member Exchange and Coworker Exchange

Abstract: Dispositional gratitude has recently emerged as a variable of interest in organizational contexts. However, it remains unclear whether dispositional gratitude is predictive of employee well-being, with limited theoretical and empirical elucidation of the underlying mechanisms. To address these limitations, the present study investigated dispositional gratitude as a predictor of employee well-being and organizational commitment. Drawing on the broaden-and-build theory of positive affect, the study also examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 129 publications
(194 reference statements)
0
6
0
Order By: Relevance
“…For example, gratitude helps to increase individuals' mindfulness-the state of open and receptive attention to their present reality, which promotes life satisfaction (Xiang & Yuan, 2021). Gratitude is positively associated with organizational commitment through leader-member exchange and coworker exchange (Zhao et al, 2023).…”
Section: Potential Indirect Roles Of Prosocial Motivation and Volunte...mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, gratitude helps to increase individuals' mindfulness-the state of open and receptive attention to their present reality, which promotes life satisfaction (Xiang & Yuan, 2021). Gratitude is positively associated with organizational commitment through leader-member exchange and coworker exchange (Zhao et al, 2023).…”
Section: Potential Indirect Roles Of Prosocial Motivation and Volunte...mentioning
confidence: 99%
“…This theory posits that positive emotions broaden individuals’ positive thought–action repertoires, thus widening the array of their thoughts and actions; this, in turn, facilitates the development of physical, psychological, and social resources. Through the application of this theory, several studies have investigated how gratitude assists individuals in expanding their thoughts and actions and developing resources, such as life satisfaction and organizational commitment, that are relevant at the individual and organizational levels (Chang et al, 2022; Kaniuka et al, 2021; Zhao et al, 2023). For example, gratitude helps to increase individuals’ mindfulness—the state of open and receptive attention to their present reality, which promotes life satisfaction (Xiang & Yuan, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the breadth of networks refers to the extent of social networks built by employees within and outside the organization (Eby et al, 2003). Previous studies have mainly focused on social networks within the organization and how leader-member exchange and coworker exchange relationships are influenced by trait gratitude (Li et al, 2022;Zhao et al, 2023). In this study, we include both internal and external networks to more comprehensively represent the breadth of the network.…”
Section: Source(s): Authors Workmentioning
confidence: 99%
“…Regulatory bodies strongly influence customer satisfaction, and warehouse measurement has the most negligible impact. (Zhao et al, 2022)Traditional and modern markets were found to have positive and significant relationships between market conduct variables. DSE participants also face a variety of obstacles, such as the impossibility of storing goods, the lack of financing, and the inconveniences associated with transportation (Davison et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%